2013
DOI: 10.1371/journal.pone.0074334
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal S6 Kinase 2 (RSK2) Maintains Genomic Stability by Activating the Atm/p53-Dependent DNA Damage Pathway

Abstract: Ribosomal S6 Kinase 2 (RSK2) is a member of the p90RSK family of serine/threonine kinases, which are widely expressed and respond to many growth factors, peptide hormones, and neurotransmitters. Loss-of function mutations in the RPS6KA3 gene, which encodes the RSK2 protein, have been implicated in Coffin-Lowry Syndrome (CLS), an X-linked mental retardation disorder associated with cognitive deficits and behavioral impairments. However, the cellular and molecular mechanisms underlying this neurological disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…For example, as identified by our previous studies and other groups, DNA damage causes phosphorylation of MDMX, followed by enhanced binding of 14-3-3 to phosphorylated MDMX, leading to the release of p53 from MDMX and subsequent activation of p53 (He et al, 2014; Jin et al, 2006; Wang et al, 2009). Also, ribosomal stress could be another outcome of DNA damage (Antoniali et al, 2014; Lim et al, 2013; Nalabothula et al, 2010), which further induces the binding of ribosomal proteins to MDM2, resulting in the disassociation of MDM2 and p53, and subsequent p53 activation (Dai and Lu, 2004; Sun et al, 2007; Zhang and Lu, 2009; Zhang et al, 2003). Inability of MDM2 or MDMX to restrain p53 through the above-mentioned pathways might be the underlying mechanisms by which DNA damage or other lesions activates p53 during the progression of some p53-related ophthalmic disorders, such as some types of cataract and microphthalmia.…”
Section: Discussionmentioning
confidence: 99%
“…For example, as identified by our previous studies and other groups, DNA damage causes phosphorylation of MDMX, followed by enhanced binding of 14-3-3 to phosphorylated MDMX, leading to the release of p53 from MDMX and subsequent activation of p53 (He et al, 2014; Jin et al, 2006; Wang et al, 2009). Also, ribosomal stress could be another outcome of DNA damage (Antoniali et al, 2014; Lim et al, 2013; Nalabothula et al, 2010), which further induces the binding of ribosomal proteins to MDM2, resulting in the disassociation of MDM2 and p53, and subsequent p53 activation (Dai and Lu, 2004; Sun et al, 2007; Zhang and Lu, 2009; Zhang et al, 2003). Inability of MDM2 or MDMX to restrain p53 through the above-mentioned pathways might be the underlying mechanisms by which DNA damage or other lesions activates p53 during the progression of some p53-related ophthalmic disorders, such as some types of cataract and microphthalmia.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of human ATM-S1981, which corresponds to mouse ATM-S1987, has been well established as a marker for human ATM kinase activation ( Bakkenist and Kastan, 2003 ) ( Shiloh and Ziv, 2013 ) ( Blackford and Jackson, 2017 ) ( Lee and Paull, 2021 ). One human anti-ATM-pS1981 antibody is commonly used to detect mouse ATM activation ( Pellegrini et al., 2006 ) ( Stracker et al., 2007 ) ( Tian and Mao, 2009 ) ( Wu et al., 2012 ) ( Lim et al., 2013 ), whereas another published antibody raised against mouse ATM-pS1987 is no longer available (Manuela Pellegrini and Andre Nussenzweig, personal communication) ( Pellegrini et al., 2006 ). We therefore used the human anti-ATM-pS1981 antibody in a time course study of ATM phosphorylation/activation following γ-irradiation of BRCA1 WT and mutant MEFs ( Brca1 WT , Brca1 S1152A/S1152A , and Brca1 S971A/S971A ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the role of mouse ATM-S1987 phosphorylation in HR-mediated repair remains controversial ( Pellegrini et al., 2006 ) ( Lee and Paull, 2021 ). The same phospho-Ser antibody raised against human ATM-pS1981 has been commonly used as a marker for mouse ATM activation ( Pellegrini et al., 2006 ) ( Stracker et al., 2007 ) ( Tian and Mao, 2009 ) ( Wu et al., 2012 ) ( Lim et al., 2013 ). To determine whether γIR-induced ATM phosphorylation as detected by the anti-human phospho-ATM antibody was indeed due to ATM-S1987 phosphorylation, we generated ATM-S1987A knockin (KI) mutation in Brca1 WT MEFs using CRISPR/Cas9 genome editing method ( Figure 5 B).…”
Section: Resultsmentioning
confidence: 99%
“…So along with the process of development and maturity, MDM2 and MDMX gradually acquire the capacity to precisely keep p53 at various levels, in an independent and/or synergistic manner (as suggested by the current study and previous studies (Xiong et al, 2007; Xiong et al, 2006; Zhang et al, 2014)), to give different cells more options to determine their fates under different stresses: irreversible death when stress is insurmountable, or survival following cell cycle arrest and DNA repair when stress is mild. Indeed, numerous studies have shown that different physiological and pathological stress signals can activate p53 by inactivating either MDM2 or MDMX via different molecules, such as ribosomal proteins on MDM2 (Antoniali et al, 2014; Lim et al, 2013; Nalabothula et al, 2010) or AMPK on MDMX (He et al, 2014), as further discussed below.…”
Section: Discussionmentioning
confidence: 99%